Zirconia-Porcelain Bonding: Effect of Multiple Firings on Microtensile Bond Strength - Trindade, Flavia Z. [UNESP]; Amaral, Marina [UNESP]; Melo, Renata M. [UNESP]; Bottino, Marco A. [UNESP]; Valandro, Luiz Felipe (Quintessence Publishing Co Inc, 2013)
Purpose: To determine the bond strength between zirconia and porcelain with varying numbers of veneer firing cycles.Materials and Methods: Fifty specimens of zirconia veneered with feldspathic ceramic were submitted to one (1-firing), two (2-firings), three (3-firings), four (4-firings), or five (5-firings) firing cycles to sinter the porcelain. After the respective number of firings, the specimens were embedded into acrylic resin and sectioned into bars with a 1-mm(2) cross-sectional area. The microbars were bonded to a special device and attached to a universal testing machine (Emic DL 1000). Microtensile bond strength testing (MTBS) was performed at 0.5 mm/min. The maximum load for fracture was recorded (N) and the microtensile bond strength was calculated in MPa. Data were analyzed using one-way ANOVA and Tukey's test (alpha = 0.05). The Weibull modulus and characteristic strength was also calculated for each experimental group.Results: Specimens submitted to a single firing cycle presented the lowest bond strength values (14.1 MPa), two firing cycles provided intermediate bond strength values (15 MPa) and the other groups presented equivalently high values (18.1 - 18.4 MPa). The Weibull modulus did not change between the groups.Conclusion: More than three firing cycles of a veneer ceramic provided higher bond strengths between zirconia and the veneering ceramic.
Keywords: all-ceramic; zirconia; layering veneer; microtensile bond strength